A novel effector secretion mechanism based on proton‐motive force‐dependent type III secretion apparatus rotation. Issue 7 (20th March 2013) - Ohgita, Takashi; Hayashi, Naoki; Hama, Susumu; Tsuchiya, Hiroyuki; Gotoh, Naomasa; Kogure, Kentaro
Abstract : The type III secretion apparatus (T3SA) participates in the secretion of bacterial proteins called effectors, although the detailed mechanism of effector secretion remains unclear. T3SA and flagellum were shown to branch from a common ancestor and also show structural similarity. In addition, both T3SA‐dependent effector secretion and flagellar rotation were reported to require proton‐motive force (PMF) for activity. From these reports, we hypothesized that T3SA, like the flagellum, would rotate via PMF and that this rotation is responsible for effector secretion. To observe T3SA rotation, we constructed a novel observation system by modifying the tip of T3SA on bacterial cell membranes with an observation probe, which allowed documentation of T3SA rotation for the first time. T3SA rotation was stopped by the addition of a protonophore that decreases PMF. Moreover, increased viscosity of the observation medium inhibited both rotation of T3SA associated with beads and effector secretion. These results suggested that effector secretion would follow the PMF‐dependent rotation of T3SA and could be inhibited by preventing T3SA rotation. Moreover, the motion‐track analysis of bead rotation suggested that the T3SA needle might be flexible. Consequently, we propose a "rotational secretion model" as a novel effector secretion mechanism of T3SA.—Ohgita, T., Hayashi, N., Hama, S., Tsuchiya, H., Gotoh, N., Kogure, K. A novel effector secretion mechanism based on proton‐motive force‐dependent type III secretion apparatus rotation. FASEB J. 27, 2862‐2872 (2013). www.fasebj.org